Cultural care theory concepts on master´s degree disertations - Boehs, Astrid Eggert; Monticelli, Marisa; Fernandes, Gisele Cristina Manfrini; Feyer, Iara Simoni Silveira; Rumor, Pamela Camila Fernandes (Rev Rene, 2010)
This a bibliographic research which aims to analyze the concepts used on master’s degree dissertations that were elaborated from the Theory of Cultural Care. We evaluated dissertations in a Program of Graduate Studies from 1990 to 2005, constituting an analytical corpus of 21 works. Starting from a script-guide, specially formulated, it was performed a descriptive analysis involving convergence and divergence among collected data, by using as interpretative basis the theory under investigation itself. The results showed that many of the concepts used in dissertations had not been presented in ipsis literis form with Leininger´s theory. Concepts were adapted in conceptual frameworks, with the intention of giving to the ideas a character of greater concreteness. It was concluded that between the deepening of theory and creative potential of nursing researchers it is vital to have fidelity to the original writings from the author.